Regional Economic Outlook, April 2010, Asia and Pacific : Leading the Global Recovery, Rebalancing for the Medium Term. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2010)
One year after the deepest recession in recent history, Asia is leading the global recovery. The Regional Economic Outlook: Asia and Pacific discusses the near-term outlook for the region, as well as the medium-term policy challenges that countries face. As in many emerging and developing markets, Asia rebounded swiftly during 2009 and in the first quarter of 2010, and in the near term the region is expected to continue leading the global recovery. In the medium term, the global crisis has highlighted the importance for Asia of ensuring that private domestic demand becomes a more prominent engine of growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet